2002
DOI: 10.1161/01.cir.0000013022.11250.30
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Murine Cardiac Allograft Arteriopathy by Long-Term Blockade of CD40-CD154 Interactions

Abstract: Background-The interaction between CD40 on antigen-presenting cells and CD40L on T cells is critical in allograft rejection. CD154 blockade suppresses allograft rejection, but the role of this pathway in allograft vasculopathy remains obscure. Methods and Results-A vascularized murine heterotopic cardiac transplant model was used to test whether perioperative CD154 blockade suppresses allograft vasculopathy or whether long-term CD154 blockade is required to suppress allograft vasculopathy. Perioperative CD154 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 19 publications
(28 reference statements)
1
35
0
Order By: Relevance
“…CD40-CD40L blockade has shown to prevent atherosclerotic plaque progression, to promote plaque stability and to prevent transplant associated vasculopathy, an accelerated form of atherosclerosis. 31,32) Our studies found that CRP, at concentration known to predict adverse cardiovascular events, caused a marked and dose-dependent increase in the cell-surface expression of CD40 and CD40L protein in HUVECs. Unstimulated HUVECs with CRP expressed lower level of CD40 and only a little CD40L, which was in accordance with previous report.…”
Section: Discussionmentioning
confidence: 77%
“…CD40-CD40L blockade has shown to prevent atherosclerotic plaque progression, to promote plaque stability and to prevent transplant associated vasculopathy, an accelerated form of atherosclerosis. 31,32) Our studies found that CRP, at concentration known to predict adverse cardiovascular events, caused a marked and dose-dependent increase in the cell-surface expression of CD40 and CD40L protein in HUVECs. Unstimulated HUVECs with CRP expressed lower level of CD40 and only a little CD40L, which was in accordance with previous report.…”
Section: Discussionmentioning
confidence: 77%
“…By specifically interrupting this dyad, A20-based gene therapy in EC could, as demonstrated using anti-CD40L Ab therapy, significantly impact on the initiation and progression of atherosclerosis and TAV. 10,11,24 …”
Section: Discussionmentioning
confidence: 99%
“…9 In animal models, CD40L blockade has been shown to prevent atherosclerotic plaque progression, promote plaque stability, and prevent transplant associated vasculopathy (TAV), an accelerated form of atherosclerosis. 10,11 We have demonstrated that the cytoprotective gene A20, prevents EC activation in response to a number of stimuli (including proinflammatory cytokines and oxidative damage) by blocking NF-B activation and shown that it protects ECs from TNF/cycloheximide-induced apoptosis through inhibition of the caspase cascade. 12,13 In this study, we evaluate the effect of A20 on CD40/CD40L-mediated EC signaling and activation.…”
mentioning
confidence: 99%
“…Echocardiographic images were recorded in a digital format. Images were then analyzed off-line by a single observer blinded to the murine genotype (29).…”
Section: Echocardiographymentioning
confidence: 99%